Direct observation of modulation structure in room-temperature multiferroic Bi4.2K0.8Fe2O9+δ. (15th April 2021) - Zhang, Lu; Tian, Huanfang; Dong, Sining; Yang, Dong; Li, Xiaoguang; Li, Jun; Li, Jianqi; Yang, Huaixin
Abstract: The coexistence and coupling between alternatively stacked layers with different functional properties often give rise to exotic physical phenomena, such as high-temperature superconductivity, multiferroic behavior, and giant thermoelectric performance, which are tightly linked with the intrinsic microstructures. Here we unambiguously uncover the structural modulations in multiferroic Bi4.2 K0.8 Fe2 O9+δ (BKFO) nanobelts with a magnetoelectric–dielectric superlattice by scanning transmission electron microscopy (STEM). The octahedrons in the perovskite layers are identified as FeO6 and the ordered arrangements of the Bi and K cations are clearly determined. Quantitative measurements of the positions of the Bi columns indicate that the displacive modulations can be decomposed into a transverse wave and a longitudinal wave, whose amplitudes and phases are layer-dependent. This study may help to understand and optimize the magnetoelectric coupling effect in BKFO. Graphical abstract: Image, graphical abstract